Potential use of Terasi, an Indonesian traditional fermented seafood paste, to provide healthy lettuce (Lactuca sativa L.) seedling - Chinta, Yufita Dwi; Sato, Tatsuo (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2023)
Terasi paste consists of plant nutrients and microorganisms that potentially improve the health of plant seedlings. We evaluated the effects of terasi paste on seed germination, seedling growth, and root rot disease severity caused by Fusarium oxysporum f.sp. lactucae (FOL) in lettuce. Terasi paste was tested at four different weights (i.e., 0.00 g [T0], 1.00 g [T1], 2.50 g [T2], and 5.00 g [T3]) in the 100 g nursery soil. The results showed that lettuce seeds from T1 and T2 treatments were fully germinated, as observed for the T0 treatment. However, 40.0% of lettuce seeds from T3 treatment failed to germinate. Thus, 1.00 g and 2.50 g terasi applications in the 100 g soil did not affect lettuce seed germination. Moreover, T1 and T2 treatments tended to improve the shoot and root biomass of lettuce seedlings over T0 treatment, while T3 treatment showed the opposite effects. Following FOL infection, the lettuce seedlings from T2 and T3 treatments had 31.1% significantly lower disease severity than those from the T0 treatment. Therefore, T2 treatment (i.e., 2.50 g terasi application in the 100 g soil) imparts maximum health-promoting benefits to lettuce seedlings.